DEPENDENCE OF SALIVARY EPITHELIAL MORPHOLOGY AND BRANCHING MORPHOGENESIS UPON ACID MUCOPOLYSACCHARIDE-PROTEIN (PROTEOGLYCAN) AT THE EPITHELIAL SURFACE - Bernfield, Merton R. (The Rockefeller University Press, 1972)
The morphogenetic role of the acid mucopolysaccharide (glycosaminoglycan) at the epithelial surface of mouse embryo submandibular glands has been studied by comparing the in vitro morphogenesis of epithelia from which the mucopolysaccharide was removed with that of those that retained the mucopolysaccharide. Epithelia isolated free of mesenchyme by procedures which retain the bulk of surface mucopolysaccharide maintain their lobular shape and undergo uninterrupted branching morphogenesis in culture in direct combination with fresh mesenchyme. Under identical culture conditions, epithelia from which surface mucopolysaccharide was removed lose their lobules and become spherical masses of tissue. During continued culture, the spherical epithelia produce outgrowths from which branching morphogenesis resumes. The morphogenetically active mucopolysaccharide is localized within the basal lamina of the epithelial basement membrane and appears to be bound to protein. During culture in combination with mesenchyme, epithelia undergoing uninterrupted morphogenesis show maximal accumulation of newly synthesized surface mucopolysaccharide at the distal ends of the lobules, the sites of incipient branching. In contrast, the material accumulates nearly equivalently over the surface of the spherical epithelia, with the exception that there is greater accumulation of the material at the surfaces of the budding outgrowths, the sites where morphogenesis will resume. Rapidly proliferating cells are localized within the lobules of epithelia undergoing uninterrupted morphogenesis, but are distributed uniformly in the cortex of the spherical epithelia, except for the outgrowths which show a greater localization of proliferating cells. It is concluded that normal salivary epithelial morphology and branching morphegenesis require the presence of acid mucopolysaccharide-protein within the epithelial basal lamina.